2021
DOI: 10.1111/jfr3.12693
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between urban planning and flooding in Port Harcourt city, Nigeria; insights from planning professionals

Abstract: Flooding is widely recognised as a global problem which has worsened in recent years due to climate change. In Nigeria, flooding remains the most widespread environmental disaster with the population of 200 million suffering numerous threats from perennial flooding. Port Harcourt in Southern Nigeria experiences annual flooding on a significant scale. While research has linked the flooding in Port Harcourt to poor urban planning, little research has engaged with planning professionals to investigate this relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…[47] conducted a questionnaire-based telephone survey. [49] explored appropriate flood-related urban planning using a qualitative approach in five steps and surveyed to investigate perceived risk (RP). RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables related to RP flooding [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] conducted a questionnaire-based telephone survey. [49] explored appropriate flood-related urban planning using a qualitative approach in five steps and surveyed to investigate perceived risk (RP). RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables related to RP flooding [50].…”
Section: Resultsmentioning
confidence: 99%
“…41 Echencu 2020 Explores how urban planning relates to flooding in Port Harcourt and reports on qualitative research conducted with five urban planners in Port Harcourt [49].…”
Section: Guo 2020mentioning
confidence: 99%
“…Human activities tied to urbanization have increased flood risks. However, the detachment of urban planning and implementation from reality worsens the problem (Echendu 2021b). Poor physical planning also manifests in the indiscriminate construction of buildings, including on drain paths and waterways in Nigeria, which contribute to flooding.…”
Section: Flooding In Nigeria and Causesmentioning
confidence: 99%
“…Furthermore, a research conducted in Nigeria by (Ede et al, 2019) revealed that several bridges failed due to flood as could be seen in Table 1. Port Harcourt being the capital of Rivers state in South-Southern Nigeria have been experiencing annual flood in a significant scale (Echendu, 2021). Although urban flooding could be caused by several factors notwithstanding, lack of good surface drainage network system is a key factor.…”
Section: Introductionmentioning
confidence: 99%